Persaingan Pengangkutan Garam Di Selat Madura 1924-1957 - Syafi'i, Imam (Citra Lekha, 2013)
This research analyzes salt production in Madura which has more intensified after the modern management carried out by the Dutch colonial in the beginning of 20th century. It has calculated by using historical methods, including heuristics, criticism, synthesis and historiography. It was also in line with increasing of salt transportation activities. The salt transportation was originally established by KPM, MSM and OJZ. However, after they were conducted a tender, Madurese sailing boat activities was increase. In the end, this situation created rivalries among them. It was also caused their eceonomy, housing, and mobilization among Madurese both inside and outside of the island. In addition, salt transportation activities affected the development of Madura’s trade network transportation. Keywords: rivalries, transportation, Madura’s salt